The Impact of Computerized Dynamic Assessment on Iranian EFL Learners' Interlanguage Pragmatic Development - Ali Zangoei; Gholamreza Zareian; Seyyed Mohammad Reza َAdel; Seyed Mohammad Reza Amirian (Journal of Modern Research in English Language Studies)
The present study reports the results of a dissertation aimed at consolidating assessment and instruction of L2 pragmatics comprehension by drawing on an interventionist computerized dynamic assessment (C-DA) through which the test was embodied by providing graduated hints (from the most explicit to the most implicit) which were standardized for all test takers. To do so, a web-based software, called a Computerized Dynamic Assessment of Speech Acts, Routines, and Implicatures (CDASRI), accessible at http://da-pragmatics.com, was developed. Then, 137 upper-intermediate or advanced high school and university students ranging in age from 16 to 36 from two provinces of Khorasan Razavi and Golestan, Iran, were selected based on convenience sampling, who voluntarily took part in the study. Based on how many hints or mediations were used by each test-taker, the CDASRI provided three scores: actual score (traditional score), mediated score, and learning potential score (LPS). The results of the study indicated that the test could improve test takers’ pragmatic comprehension competence. Moreover, the significant difference between the mediated (using hints) and actual (without hints) scores of learners accounted for the fact that because of test-takers’ different Zone of Proximal Development (ZPD) levels, their level of responsiveness to mediation was significantly different from one another. Hence, it can be concluded that traditional non-dynamic test loses sight of a big part of learners’ abilities through neglecting learners’ potentialities and putting emphasis only on their preliminary performance. The study concludes with some pedagogical implications for language teachers and instructors who seek an effective perspective for their assessment and instruction.